Modulation of intrinsic neuronal excitability 1 - Spruston, Nelson (Henry Stewart Talks, 2011)
Synaptic integration and action potential firing, Neuromodulation, Modulation of firing by activation of GPCRs, Modulation by other mechanisms, Targets of modulation, Modulation activity in the thalamus, Long-term plasticity of intrinsic excitability -Local control of excitability